Firm-bank linkages and optimal policies after a rare disaster - Segura, Anatoli; Villacorta, Alonso (Journal of Financial Economics, 2023)
We study optimal government support following a rare disaster that creates heterogeneous firm liquidity needs. Firms’ increase in debt reduces their output due to moral hazard. Banks are subject to a minimum capital requirement that limits deposit insurance costs upon bad aggregate shocks. Without government support, firms’ moral hazard and banks’ funding frictions reinforce each other amplifying output losses. Optimal support is implemented with firm-specific transfers combined with the provision of aggregate risk insurance through a capital requirement relaxation and a public preferred equity stake in banks. Our results shed light on suboptimality features in the actual policy responses to Covid-19 lockdowns.